2011
DOI: 10.1158/1078-0432.ccr-10-2049
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Investigation of Permeability and Distribution of Macromolecules in Mouse Malignant Transformation Using PET

Abstract: Purpose: We apply positron emission tomography (PET) to elucidate changes in nanocarrier extravasation during the transition from premalignant to malignant cancer, providing insight into the use of imaging to characterize early cancerous lesions and the utility of nanoparticles in early disease.Experimental Design: Albumin and liposomes were labeled with 64 Cu (half-life 12.7 hours), and longitudinal PET and CT imaging studies were conducted in a mouse model of ductal carcinoma in situ. A pharmacokinetic model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 44 publications
2
31
1
Order By: Relevance
“…The IRDye 800CW-to-albumin ratio ([A 780 /ε dye ]/[(A 280 -(0.03 × A 780 ))/ε Albumin ], ε dye = 270,000 M -1 cm -1 , ε Albumin = 43,824 M -1 cm -1 ) was calculated to be 0.91. The resulting IRDye 800 CW-labeled albumin has a similar circulation profile as that reported previously [38, 45], retaining 8% ID/cc (injected dose per cubic centimeter of blood) at 18-24 h post injection.…”
Section: Methodssupporting
confidence: 72%
See 1 more Smart Citation
“…The IRDye 800CW-to-albumin ratio ([A 780 /ε dye ]/[(A 280 -(0.03 × A 780 ))/ε Albumin ], ε dye = 270,000 M -1 cm -1 , ε Albumin = 43,824 M -1 cm -1 ) was calculated to be 0.91. The resulting IRDye 800 CW-labeled albumin has a similar circulation profile as that reported previously [38, 45], retaining 8% ID/cc (injected dose per cubic centimeter of blood) at 18-24 h post injection.…”
Section: Methodssupporting
confidence: 72%
“…In addition, fluorescence imaging of conjugates, such as albumin bound to a fluorescent dye, can be applied to image the extravasation and accumulation of larger molecules [35]. Albumin is typically retained within the vasculature to maintain osmotic pressure, thus its extravasation is a widely-used measure of alterations in permeability [36-38]. …”
Section: Introductionmentioning
confidence: 99%
“…Because of our interest in looking at lymphatics as well as the trafficking of macrophages, a syngeneic, orthotopic model was appropriate. As we have previously observed for 64 Cu-lipsosomal uptake in mouse mammary intraepithelial neoplasia outgrowth (MIN-Os) tumors 42 and MET-1 mammary carcinoma 43 , the accumulation of 89 Zr liposomes was primarily concentrated in the peripheral region of the tumor, reflecting the angiogenic status of the tumor periphery.…”
Section: Discussionmentioning
confidence: 51%
“…Karathanasis et al effectively correlate tumor accumulation of iodinated liposomes to markers of blood vessel permeability (i.e., VEGF and VEGF receptor-2) [58], as well as therapeutic efficacy of doxorubicin-loaded liposomes in a separate report [15]. Other studies have demonstrated the impact of nanosystems, tumor properties, and modulating interventions on assessing the status and exploitation of the EPR effect at the whole-tumor level [14,[59][60][61]. Beyond the goal of achieving maximum tumor accumulation macroscopically -for which the direct impact on antitumor efficacy remains elusive -achievement of a favorable underlying micro-accumulation of nanomedicines may contribute significantly to an overall anti-tumor response.…”
Section: Discussionmentioning
confidence: 99%